The governance of the City University of New York : a system at odds with itself - Gill, Brian P., 1968-; Rand Corporation; RAND Education Program (Santa Monica, CA : RAND, 2000)
This report, commissioned by the Mayor's Advisory Task Force on the City University of New York (CUNY), examines CUNY's system of governance and concludes that it is dysfunctional from the top to the bottom. Battles for leadership among CUNY's stakeholders have become increasingly rancorous. Lines of responsibility are tangled and poorly defined. CUNY colleges often act more like independent institutions than like complementary members of a system. Despite this independence, competition fails to lead to improvement, because incentives for institutional and individual performance are weak. Although many university systems around the country are plagued by similar structural problems, CUNY's problems appear to be especially severe. Policymakers are demanding improvement in CUNY's performance of its educational mission, but they should be aware that substantial improvements in educational outcomes are unlikely to be achieved and sustained without basic reforms of governance.
"RAND Education."
Includes bibliographical references (p. 63-68).
Also available on the internet via WWW in PDF format.
Keywords: City University of New York -- Administration; City University of New York -- Planning